Effect of Drying on Chemical Composition and Antioxidant Activity of Fruits of Momordica dioica (Kankoda) - Nehra, Sukriti; Deen, M.K. (Asian Journal of Chemistry, 2016)
The fruit of Momordica dioica (Kankoda) is a seasonal vegetable and its availability is limited to certain pockets of the country. In order to make it available throughout the year in adequate quantity, these are used in dried form. So our aim was to study the effect of drying on chemical composition and antioxidant activity of fruits of Kankoda. In the present study, fresh and dried fruits were extracted with acetone, ethanol and water separately and the extracts were evaluated for total phenolics, flavonoids and ascorbic acid content on dry mass basis. Their antioxidant activities were determined by the 2,2'-diphenyl-1-picrylhydrazyl (DPPH•) free radical scavenging method, b-carotene bleaching method (BCBT) and ferric thiocyanate (FTC) method. Total flavonoids (3.81 ± 0.20 mg CAE/g) and ascorbic acid (0.63 ± 0.01 mg/g) were highest in acetone extract while total phenolic content (5.45 ± 0.26 mg GAE/g) was highest in the water extracts of fresh fruits. Total phenolics (3.58 ± 0.09 mg GAE/g), flavonoids (4.22 ± 0.13 mg CAE/g) and ascorbic acid (0.35 ± 0.01 mg/g) were highest in acetone extract of dried fruits. The flavonoids increased in the acetone extract of dried fruit as compared to the fresh fruit. The antioxidant activity of ethanol extract by DPPH method was found to be maximum (87.02 ± 0.04 %) while in ferric thiocyanate method and b-carotene bleaching method, it was maximum for acetone extract (65.36 ± 1.28 %) and (70.43 ± 0.75 %), respectively for the extracts of fresh fruits. The antioxidant activity of the acetone extract of dried material was maximum (89.03 ± 0.75 %) according to DPPH method and (75.21 ± 1.12 %) by b-carotene bleaching method respectively. Out of these three extracts with acetone, ethanol and water the acetone extracts in general showed maximum antioxidant activity and can be used as a source of antioxidant in foods and medicines.